Trade Sensitivity to Exchange Rates in the Context of Intra-Industry Trade - Oguro, Yoko (IMF Working Papers; Working Paper ;, 2008)
This paper theoretically and empirically investigates export sensitivity to exchange rates in the context of intra-industry trade (IIT). It is assumed that more IIT implies a smaller elasticity of substitution among differentiated products and vice versa. The model presented suggests the gap in production costs between two countries has an influence on IIT as well. Industry-level pane regressions of thirty-eight trading pairs provide strong empirical support for the idea that the exchange rate sensitivity of exports declines in concert with the extent of ITT. An obvious policy implication is that the effectiveness of exchange rates in addressing trade imbalances will diminish as the extent of IIT increases.